2003
DOI: 10.1002/adfm.200304320
|View full text |Cite
|
Sign up to set email alerts
|

Electroactivity of Polyaniline Multilayer Films in Neutral Solution and Their Electrocatalyzed Oxidation of β‐Nicotinamide Adenine Dinucleotide

Abstract: In this paper, we report an alternative simple method to shift the electroactivity of polyaniline (PANI) films to neutral pH conditions by forming multilayer assemblies with poly(anions) using the layer‐by‐layer (LBL) deposition method. A series of self‐assembled PANI multilayer films with poly(anions), such as sulfonated polyaniline (SPANI), poly(acrylic acid) (PAA), poly(vinyl sulfonate) (PVS), and poly(styrene sulfonate) (PSS), were prepared by the LBL method. Their electrochemical behavior and catalytic ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
114
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(119 citation statements)
references
References 41 publications
4
114
1
Order By: Relevance
“…The EC-SPPL method can be acted as a sensitive tool for detection the photoluminescence from a conjugated polymer film and could have potentials for sensors and optoelectronic devices applications. An electroactivity of polyaniline (PANI) films in neutral pH condition and their electrocatalyzed oxidation of β-nicotinamide adenine dinucleotide (NADH) were also reported by Tian et al [23]. Self-assembled PAIN multilayer films by forming with poly(anion) such as sulfonated polyaniline (SPANI), poly(acrylic acid) (PAA), poly(vinyl sulfonate) (PVS), and poly(styrene sulfonate) (PSS) were prepared using layer-by-layer (LBL) method.…”
Section: Electrochemical Spr For Monitoring Of Conducting Polymer Thimentioning
confidence: 90%
See 1 more Smart Citation
“…The EC-SPPL method can be acted as a sensitive tool for detection the photoluminescence from a conjugated polymer film and could have potentials for sensors and optoelectronic devices applications. An electroactivity of polyaniline (PANI) films in neutral pH condition and their electrocatalyzed oxidation of β-nicotinamide adenine dinucleotide (NADH) were also reported by Tian et al [23]. Self-assembled PAIN multilayer films by forming with poly(anion) such as sulfonated polyaniline (SPANI), poly(acrylic acid) (PAA), poly(vinyl sulfonate) (PVS), and poly(styrene sulfonate) (PSS) were prepared using layer-by-layer (LBL) method.…”
Section: Electrochemical Spr For Monitoring Of Conducting Polymer Thimentioning
confidence: 90%
“…Several techniques coupled to electrochemistry have been developed to study the properties of polymer films such as quartz crystal microbalance (QCM) [15], Fourier transform-infrared (FT-IR) spectroscopy [16], electron spin resonance (ESR) [17], and surface plasmon resonance (SPR) spectroscopy [18,19]. SPR spectroscopy is the technique for monitoring the change of the refractive index at a solid-liquid interface, which has been widely used for the characterization and study of polymer films, interfaces, and kinetic processes at surfaces [20][21][22][23]. Recently, the combination of SPR and electrochemical, named electrochemicalsurface plasmon resonance (EC-SPR) spectroscopy, have been used for in situ investigation of optical and electrical properties of conducting polymer films [24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Research interest has also grown in the synthesis of multifunctional nanomaterials with conjugated polymer hybrids, such as colloids, films, and bulk materials, through sol-gel synthesis [5][6][7], electrochemical deposition [8][9][10], or photochemical deposition [11]. These hybrid materials have attracted such growing interest because of their superior properties as electro-catalysts [12,13], memory devices [14], and electrochemical supercapacitors [15] compared with those of pure polymeric materials.…”
Section: Introductionmentioning
confidence: 99%
“…The peaks merged upon increasing the pH of the medium, as shown in Figure 8Be and Bf. Tian et al 46 reported that the merging of the peaks usually occurred at pH .5. PANI has been reported to lose its electrochemical activity in the neutral or basic medium.…”
Section: Electrochemical Propertiesmentioning
confidence: 99%
“…Two pairs of redox peaks were distinctly visible for ITO/SG-PANI when the CV was measured in the presence of 1 M HCl ( Figure 8A), which is in agreement with earlier published reports. 46,47 These peaks correspond to the variable oxidation states of PANI. The peaks merged upon increasing the pH of the medium, as shown in Figure 8Be and Bf.…”
Section: Electrochemical Propertiesmentioning
confidence: 99%